Pan-cerebral sodium elevations in vascular dementia: Evidence for disturbed brain-sodium homeostasis - Philbert, Sasha A.; Xu, Jingshu; Church, Stephanie J.; Unwin, Richard D.; Roncaroli, Federico; Cooper, Garth J. S. (Frontiers in Aging Neuroscience, 2022)
Vascular dementia (VaD) is the second most common cause of cognitive impairment amongst the elderly. However, there are no known disease-modifying therapies for VaD, probably due to incomplete understanding of the molecular basis of the disease. Despite the complex aetiology of neurodegenerative conditions, a growing body of research now suggests the potential involvement of metal dyshomeostasis in the pathogenesis of several of the age-related dementias. However, by comparison, there remains little research investigating brain metal levels in VaD. In order to shed light on the possible involvement of metal dyshomeostasis in VaD, we employed inductively coupled plasma-mass spectrometry to quantify the levels of essential metals in post-mortem VaD brain tissue (n = 10) and age-/sex-matched controls (n =10) from seven brain regions. We found novel evidence for elevated wet-weight cerebral sodium levels in VaD brain tissue in six out of the seven regions analysed. Decreased cerebral-potassium levels as well as increased Na/K ratios (consistent with high tissue sodium and low potassium levels) were also observed in several brain regions. These data suggest that reduced Na+/K+-exchanging ATPase (EC 7.2.2.13) activity could contribute to the contrasting changes in sodium and potassium measured here. In addition, multiregional elevation of cerebral-sodium levels highlights the potential application of Na as a diagnostic biomarker in VaD patients, which may also assist in the ante-mortem discrimination of VaD from AD.